Serum proteinogram in sheep with acute ruminal lactic acidosis - Sabes, Amanda F. [UNESP]; Girardi, Annita M. [UNESP]; Fagliari, Jose J. [UNESP]; Oliveira, Joao A. de [UNESP]; Marques, Luiz C. [UNESP] (Cairo Univ, 2017)
The electrophoretic fractionation represents one of the most reliable methods for the identification of blood proteins in ruminants. The aim of this study was to evaluate the serum proteinogram of sheep with acute ruminal lactic acidosis (ARA) using the SDS-PAGE electrophoresis technique. Ten Santa Ines ewes were used and blood was collected to establish the basal values for induction of ARA. Sucrose was administered orally in a single dose of 15 g/kg body mass. After the administration, blood samples were obtained at the following moments: 4, 8, 12, 16, 20, 24, 28, 32, 36, 48, 72, 96, 120 and 144 h. Subsequently, samples were obtained every seven days for three further weeks, until complete one month. The total of 13 proteins were identified: immunoglobulins A and G, ceruloplasmin, transferrin, albumin, alpha 1-antitrypsin, haptoglobin, alpha 1-acid glycoprotein, proteins of molecular weight 95, 46, 36 and 31 kDa. The increase of haptoglobin from 08 h coincides with the ruminal pH decrease, possibly due to the death of Gram negative bacteria and also the inflammatory process on the rumen. Fibrinogen was presented on highest mean at 48 h and returned to normal with 144 h. We can conclude that changes in serum levels of acute phase proteins can assist the clinical evaluation and diagnosis of ARA in sheep. (C) 2017 Faculty of Veterinary Medicine, Cairo University. Production and hosting by Elsevier B.V.
Keywords: Electrophoresis; Haptoglobin; Proteins; Inflammation; Santa Ines; Sheep; Ruminal lactic acidosis